2022
DOI: 10.1515/med-2022-0515
|View full text |Cite
|
Sign up to set email alerts
|

miR-212-5p inhibits nasopharyngeal carcinoma progression by targeting METTL3

Abstract: This study was conducted to investigate the effect of microRNA-212-5p (miR-212-5p) on the proliferation and apoptosis of nasopharyngeal carcinoma (NPC) cells. Microarray datasets (EXP00394 and EXP00660) were downloaded from the dbDEMC database, and the differentially expressed microRNAs between high-grade and low-grade NPC were analyzed. miR-212-5p and methyltransferase like 3 (METTL3) expression levels in NPC tissues and cells were determined by the quantitative real-time polymerase chain reaction and Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This has become strong epiphenomenal evidence in this article to understand the process of apoptosis caused by cowshed PM 2.5 . It is undeniable that miR-212-5p regulates multiple target genes, which have the same or different functions [ 32 , 46 , 47 ], all of which suggest that miR-212-5p has complex biological functions depending on the target genes and cellular context. Some articles have reported that miR-212-5p can regulate some physiological activities, such as cell proliferation and epithelial mesenchymal transition [ 48 , 49 ], but the regulation of apoptosis after cowshed PM 2.5 stimulation by miR-212-5p has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This has become strong epiphenomenal evidence in this article to understand the process of apoptosis caused by cowshed PM 2.5 . It is undeniable that miR-212-5p regulates multiple target genes, which have the same or different functions [ 32 , 46 , 47 ], all of which suggest that miR-212-5p has complex biological functions depending on the target genes and cellular context. Some articles have reported that miR-212-5p can regulate some physiological activities, such as cell proliferation and epithelial mesenchymal transition [ 48 , 49 ], but the regulation of apoptosis after cowshed PM 2.5 stimulation by miR-212-5p has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…26 In our investigation, based on bioinformatics analysis, miR-212-5p was screened and verified to bind with LINC00599 in 16HBE cells. As an important member of the miR family, miR-212-5p has been reported to be dysregulated in a variety of human diseases, such as non-alcoholic fatty liver disease, 27 nasopharyngeal carcinoma, 28 and ovarian cancer. 29 For example, circ_0,099630 curbed periodontal ligament cells proliferation and osteogenic differentiation through elevating SPRY1 expression via sponging miR-212-5p in periodontitis.…”
Section: Discussionmentioning
confidence: 99%